Cutaneous nontuberculous mycobacterial infection in Thailand: A 7-year retrospective review - Phatcharawat Chirasuthat (2020)
A remarkable increase in the prevalence of cutaneous nontuberculous mycobacterial (NTM) infection has occurred worldwide. However, updated data regarding cutaneous NTM infection in Thailand is limited.This study aim to describe the clinical manifestations, pathogenic organism, and prognostic factors of cutaneous NTM infections among patients living in Thailand.The electronic medical records of all patients with confirmatory diagnosis of cutaneous NTM infection from either positive cultures or polymerase chain reaction were retrospectively reviewed at a university-based hospital.From 2011 to 2017, a total of 88 patients with a confirmed diagnosis of cutaneous NTM infection were included. Mycobacterium abscessus was the most common pathogens followed by M haemophilum and M marinum (61.4%, 10.2%, and 8.1%, respectively). Nodule and plaque were 2 most common lesions (26.4% and 25.5%, respectively) and lower leg is the most common site of involvement (50.9%). The majority of patients presented with single lesion (67%). Seven patients (7.9%) had history of surgical procedure and/or cosmetic injection before the development of lesion and all pathogenic organisms in this group were rapidly growing mycobacteria. Sweet's syndrome and erythema nodosum were the 2 most common reactive dermatoses, presented in 3.4% and 2.3%, respectively. The majority of patients infected with cutaneous M haemophilum infections were immunocompromised and lacked history of preceding trauma (77.8%). Patients with cutaneous NTM that receiving less than 3 medications was associated with higher disease relapse (odds ratio 65.86; P = .02).M abscessus is the most common pathogen of cutaneous NTM infection in Thailand. The prevalence of M haemophilum is increasing and should be particularly cautious in immunocompromised patients. Rapidly growing mycobacteria should be suspected in all cases of procedure-related cutaneous NTM. We recommend at least 3 antibiotics should be considered for cutaneous NTM infection to reduce the rate of relapse.